Biological movement variability during the sprint start - Bradshaw, E. J.; Maulder, P. S.; Keogh, J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The current study proposed a method for estimating biological movement variability in order to examine its effect on 10 m sprinting performance. Two 250 Hz cameras recorded the sprinters (male, n=10) action across four trials to enable the kinematics of their block start and initial strides to be obtained using motion analysis software (APAS). Infra-red timing lights were utilised to measure the 10 m sprinting times. The coefficient of variation (CV %) calculation was adjusted in order to separate biological movement variability (BCV %) from variability induced by measurement error (SEE %). This adjustment revealed that measurement error highly inflated traditional measures of movement variability (CV %) by up to 72%,. Variability in task outcome kinematics was considerably lower than that observed in joint rotation patterns. Few biological variability measures had a direct relationship with reduced sprinting time.